Pengaruh Permainan Tradisional Balakeh Terhadap Gerak Dasar Siswa Tunagrahita Ringan di SDN Gayungan 2/423 Surabaya - Dwi Hatmono; Doni Satria Nugraha; Dwi Sudiyanto Z; Dwiki Syaibatul H; Masitha Surya A; Heryanto Nur Muhammad; Mohammad Hoiri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to investigate the impact of the traditional game Balakeh on the improvement of basic motor skills in students with mild intellectual disabilities at SDN Gayungan 2 Surabaya. The research employed a Classroom Action Research (CAR) approach with a One-Group Pretest-Posttest Design, involving 12 students with mild intellectual disabilities from grades 4, 5, and 6. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The instruments used to measure basic motor skills included the Zig-Zag Run Test (agility), Static Flexibility Test (flexibility), and Standing Stork Test (balance). The results showed a significant improvement in all three aspects of motor skills after the implementation of the Balakeh game. On agility, the average time decreased from 11.13 seconds to 10.56 seconds, flexibility increased from 20.96 cm to 22.23 cm, and balance improved from 16.52 seconds to 17.45 seconds. The percentage of students meeting the completion criteria also increased, with agility reaching 83.33%, flexibility 91.67%, and balance 75%. These findings indicate that the Balakeh game is effective in enhancing basic motor skills in students with mild intellectual disabilities and can be integrated into adaptive PJOK education for children with special needs.